New Data on the Genus Axonopsis Piersig, 1893 (Acari: Hydrachnidia, Aturidae) in Turkey - Esen, Yunus; Kaya, Yucel; Erman, Orhan (Inst Zoology, Bas, 2015)
New records of the water mites of the genus Axonopsis Piersig, 1893 (Acari: Hydrachnidia, Aturidae) from Siirt Province, Turkey, are presented in this paper. Two subgenera and three species are newly recorded to the Turkish fauna, i.e. Axonopsis (Axonopsis) complanata (Muller, 1776), A. (Brachypodopsis) guadarramensis Valdecasas, 1981 and A. (Brachypodopsis) inferorum Motas, Tanasachi, 1947. In addition, two previously reported species from Turkey, A. (Hexaxonopsis) serrata Walter, 1928 and A. (Navinaxonopsis) persica Peke, 2004 are also found in Siirt Province.
Keywords: Acari; Siirt Province; Axonopsis; new records; Turkey